The diachronic analysis of pastoralism through comparative variables - Nixon, L; Price, S; Price, S (British School at Athens, 2001)
Diachronic analyses of pastoralism over the millennia pose a problem. Studies of one period can use models based on other periods as heuristic devices, to pose problems and questions for investigation. But survey archaeologists and others engaged in diachronic analysis cannot assume a period-specific model as a starting point. Instead, we propose that investigation begin from a set of seven variables, which constitute the elements for the formulation of comparative analyses: environment; location; scale; specialisation; links with agriculture; gender/division of labour; and cultural integration. The first five have been discussed before in the literature, but the last two have not previously been given sufficient attention, because of the old dominance of environmental and economic preoccupations.